2011
DOI: 10.1212/wnl.0b013e318207b060
|View full text |Cite
|
Sign up to set email alerts
|

MHC transmission

Abstract: Objective: Major histocompatibility complex (MHC) genes dominate genetic susceptibility factors in multiple sclerosis (MS). Given the general consensus that incidence and prevalence of MS has been rising and specifically in women, we evaluated MHC-gender interactions. Methods:In a large family-based cohort consisting of 7,093 individuals (2,127 affected individuals) from 1,055 MS families, we examined MHC transmission by family structure and gender stratified by genetic distance of affected relatives from the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
38
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(40 citation statements)
references
References 33 publications
1
38
0
1
Order By: Relevance
“…16,17 The selection of these particular alleles was based on previous studies in which they have been reported to be implicated as part of haplotypes conferring the highest risk or protection scores5. 18 Brief description: DRB1* 0401-0411-0301-1501-1502 -0101-0103 -0102 -0701-0702 -1001 -1101-1104 -1401-1404 1403, DQB1* 0602, DQA1* 0301, *0102. A primer pair to amplify the third intron of DRB1 genes was included in each PCR reaction as the internal positive control.…”
Section: Hla Typingmentioning
confidence: 99%
See 1 more Smart Citation
“…16,17 The selection of these particular alleles was based on previous studies in which they have been reported to be implicated as part of haplotypes conferring the highest risk or protection scores5. 18 Brief description: DRB1* 0401-0411-0301-1501-1502 -0101-0103 -0102 -0701-0702 -1001 -1101-1104 -1401-1404 1403, DQB1* 0602, DQA1* 0301, *0102. A primer pair to amplify the third intron of DRB1 genes was included in each PCR reaction as the internal positive control.…”
Section: Hla Typingmentioning
confidence: 99%
“…These two primers matched non-allelic sequence. 17,18 All primers were obtained from the Department of oligonucleotide synthesis, at Center of Genetic Engineering and Biotechnology (Havana, Cuba), and used at 0.25 µM. Amplified products were separated by electrophoresis in 2 % agarose gels containing ethidium bromide after the addition of loading buffer, and visualized using UV illumination.…”
Section: Hla Typingmentioning
confidence: 99%
“…19 In subsequent studies, interestingly, the major MS risk allele human leukocyte antigen (HLA)-DRB1*15 was found to be preferentially transmitted from mothers to affected female offspring. [20][21][22][23] These studies suggested that this preferential maternal transmission of the major histocompatibility complex (MHC) risk allele is the molecular basis of the maternal parent-of-origin effect in MS, and emphasized the involvement of epigenetic mechanisms in MS heritability. [20][21][22][23] These findings are quite solid, and the idea is attractive in that part of the missing heritability of MS can be explained by epigenetics.…”
Section: Epidemiology Implicating Involvement Of Epigenetics In Msmentioning
confidence: 99%
“…[20][21][22][23] These studies suggested that this preferential maternal transmission of the major histocompatibility complex (MHC) risk allele is the molecular basis of the maternal parent-of-origin effect in MS, and emphasized the involvement of epigenetic mechanisms in MS heritability. [20][21][22][23] These findings are quite solid, and the idea is attractive in that part of the missing heritability of MS can be explained by epigenetics. However, the molecular basis for the parent-of-origin effect in MS, and how epigenetic mechanisms can skew not only the transmission of phenotype, but also the MHC genotype is not clear.…”
Section: Epidemiology Implicating Involvement Of Epigenetics In Msmentioning
confidence: 99%
“…Underlying gender-related factors might be hormonal or environmental or due to gene-environment interactions. 9 Changes in women's lifestyle (i.e. use of contraceptives, dietary changes, obesity, smoking behaviour, roles in the workforce, sunlight exposure, vitamin D deficiency) and in particular higher age at first childbirth or fewer pregnancies could contribute to the increasing incidence of MS in women.…”
mentioning
confidence: 99%